"INIVIT C-2000": Nueva variedad de calabaza (Cucurbita moschata Duch) para condiciones tropicales - Ruiz Diaz, E.=700 1 Cruz, J.A.; Rodriguez, S.; Perez, R.; Averhoff, N.; Rivera, C.M.; Fabelo, E.; Arcia, O.; Cartalla, G.; Oliva, M.; Ventura, J. de la C.; Maza, N.
(Es, En)
Ilus., 7 ref.
Keywords: CUCURBITA MOSCHATA; VARIEDADES; ANALISIS DIALELO; FITOMEJORAMIENTO; CUBA; CALABAZA